2010
DOI: 10.1016/j.jmaa.2010.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal sequences and regularity of embeddings into finite-dimensional spaces

Abstract: This paper focuses on the regularity of linear embeddings of finite-dimensional subsets of Hilbert and Banach spaces into Euclidean spaces. We study orthogonal sequences in a Hilbert space H, whose elements tend to zero, and similar sequences in the space c 0 of null sequences. The examples studied show that the results due to Hunt and Kaloshin (Regularity of embeddings of infinite-dimensional fractal sets into finitedimensional spaces, Nonlinearity 12 (1999) 1263-1275) and Robinson (Linear embeddings of finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…(4) Is the exponent γ in Theorem 5.6 (the power of the slog term) in any way optimal? (Pinto de Moura & Robinson [19] show that one can do no better than γ > 1 2 in general.) (5) Can one bound the Assouad dimension of the attractors of dissipative PDEs (or preferably the set of differences of solutions lying on such attractors)?…”
Section: Resultsmentioning
confidence: 99%
“…(4) Is the exponent γ in Theorem 5.6 (the power of the slog term) in any way optimal? (Pinto de Moura & Robinson [19] show that one can do no better than γ > 1 2 in general.) (5) Can one bound the Assouad dimension of the attractors of dissipative PDEs (or preferably the set of differences of solutions lying on such attractors)?…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the beginning of the section, we do not know if the dual thickness is always bounded above by the box-counting dimension. However, Pinto de Moura and Robinson [14] relied on this fact to prove that the dual thickness and box-counting dimension of these orthogonal sequences coincide for every p ∈ [1, ∞]. In the next lemma, we show that this upper bound is true in this particular case.…”
Section: 'Orthogonal' Sequences In ℓ Pmentioning
confidence: 77%
“…In the remainder of this paper, we concentrate on a particular subset of ℓ p , for p ∈ [1, ∞], and prove that some of the inequalities we know so far are sharp. These sets were first discussed by Ben Artzi et al [3] and have been used by Pinto De Moura & Robinson [14] as examples to show that the Hölder exponent of the inverses in Hunt and Kaloshin's Theorem 1.5 is asymptotically sharp. Take p ≥ 1 and let (α n ) ∞ n=1 be a decreasing sequence such that α n → 0.…”
Section: 'Orthogonal' Sequences In ℓ Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinto de Moura and Robinson (2010a) showed that this bound on the logarithmic exponent γ in Theorem 4.1 is sharp as m −→ ∞. 2 The term 'prevalence' was coined by Hunt et al (1992) and generalizes the notion of 'Lebesgue almost every' from finite to infinite-dimensional spaces.…”
Section: Embedding the Dynamics On A Into Euclidean Spacementioning
confidence: 99%